Lifetime Receipt of Inheritances and the Distribution of Wealth in England1. (March 2016) - Crawford, Rowena; Hood, Andrew
Abstract: We investigate the impact of inheritances and gifts received on the distribution of wealth. Whereas previous work has looked only at marketable wealth, we consider broader measures of wealth including state and private pensions. We find that once pension wealth is included, inheritances and gifts no longer have an equalising impact on the distribution of wealth. Without pension wealth, including wealth transfers reduces the Gini coefficient for wealth from 0.57 to 0.52. With pension wealth, the impact is negligible. We argue that this latter effect gives a better indication of the impact of inheritances on the distribution of lifetime income.